Delayed Epistaxis which Was Developed after Orthognathic Surgery with Le Fort I Osteotomy and Managed by Endoscopic Cauterization - Yuya Kurasawa; Hitoshi Sato; Ryogo Katada; Takanobu Inada; Tatsuo Shirota; Toshikazu Shimane (Case Reports in Dentistry)
A case of delayed epistaxis from the mucosa behind the right side of the inferior nasal mucosa 11 days after orthognathic surgery by Le Fort I osteotomy is presented. The patient was a 31-year-old man who underwent orthognathic surgery under general anesthesia. No abnormal findings were found during or after the operation. The patient was discharged from the hospital 10 days postoperatively. However, bleeding from the right nasal cavity occurred suddenly on the night after discharge, and he presented to our hospital again. The epistaxis was stopped once by nasal packing containing 0.001% epinephrine and systemic infusion of carbazochrome sulfonic acid and tranexamic acid. However, when the nasal packing was removed the next day, right nasal epistaxis was observed again. Curvature of the nasal septum and thickening of the inferior turbinate mucosa were seen on inspection; although, no active bleeding point was identified. Decreased nasal mucosa thickening and bleeding were observed after nasal packing containing 0.02% epinephrine. When the inside of the nasal cavity was observed endoscopically, an approximately 2 mm laceration was found in the mucosa behind the side wall of the right inferior nasal mucosa, and bleeding from the same part was confirmed. After endoscopic cauterization for hemostasis of the nasal mucosa, no rebleeding was observed. Although delayed epistaxis after Le Fort I osteotomy are often performed CT angiography to confirm the bleeding site, endoscopic cauterization would be primarily useful because of less invasiveness.